Pengaruh Kemudahan Penggunaan,Kualitas Pelayanan,Persepsi Keamanan Terhadap Keputusan Penggunaan BRImo Pada Mahasiswa Universitas HKBP Nommensen Medan - Tambunan, Debora; Sihombing, Natalia E.; Rajagukguk, Jonson (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study was conducted to examine the impact of ease of use, service quality, and security perception on the decision to use BRImo among students at the University of HKBP Nommensen Medan. The type of research used is quantitative research, with data collection through the distribution of questionnaires. The population in this study is the students of the University of HKBP Nommensen Medan. The sample calculation in this study uses the Slovin formula, resulting in 98 respondents. The sampling method used is a non-probability method with quota sampling technique. The data analysis technique uses SPSS 25.0. This study has met validity and reliability tests. The data analysis used in this study includes classical assumption tests, multiple linear regression tests, statistical tests, and coefficient of determination. The results of this study indicate that the variables of ease of use, service quality, and security perception have a significant impact both simultaneously and partially on the decision to use BRImo among students at the University of HKBP Nommensen Medan.